Ex vivo correlation of ultrasonographic appearance of gastric submucosal fat with histology in cats - Teoh, Yong Bin (2017)
Background: Ultrasonographic assessment of the stomach and its layers are performed routinely in companion animals. Varying submucosal thicknesses are seen in cats ultrasonographically, however their attribution to fat deposition, anatomical variation or disease processes remain unknown. Hypothesis/Objective: To correlate appearance of gastric submucosa on ultrasound with its histology in cats. Animals: 25 cats from animal shelters and pounds. Methods: Following humane euthanasia for various reasons, the stomach was resected and ex-vivo ultrasonography was performed at the fundus, body and pylorus. Ultrasound measurements include thickness of gastric wall (GWUS) and submucosa (GSMUS). Gastric rugae fold (RF) presence was also recorded. Thereafter, histology of the stomach section measured at ultrasound was performed. Histological measurements include thickness of gastric wall (GWH) and submucosa (GSMH) and submucosa fat score (GSMFAT).Results: Fat was present in the gastric submucosa in 96% of cats. However, no association was found between GSMUS and GSMFAT in all regions. GSMUS was correlated to GSMH (r=0.459; P =0.021) in the body. RF was associated to GSMUS in fundus and body. Conclusion: Gastric submucosal thickness is not associated to fat deposition on histology. Nevertheless, ultrasonographic thickness in gastric submucosa corresponds to histology and was also associated to presence of rugae fold.